Construct validation of consumer complaint behavioral scale in the Malaysian mobile phone services industry - A. Rahman, Mohd. Khirzan Badzli; Haron, Sharifah Azizah; Paim, Laily; Othman, Mumtazah; Osman, Syuhaily; Othman, Abdul Kadir (Canadian Center of Science and Education, 2015)
Consumer Complaint Behavior (CCB) is a topic that is continuously being studied globally at various types of industries and from different perspectives. Nevertheless, CCB has varying definitions and different conceptualizations used among the researchers. Public Action, Private Action, No Action and Voice are among the underlying constructs that are frequently used by the researchers to represent CCB. This paper attempts to further clarify the possible and valid constructs of CCB based on the result of EFA and CFA for complainers and non-complainers. SPSS version 21 and AMOS version 21 were used to analyze the data and the results of Goodness of Fit, Average Variance Extracted have met the suggested threshold values. The study also revealed the existence of four factors of CCB for complainers and two factors for non-complainers.